IMMU-11. RESPONSE OF T-CELLS UNDER THE INFLUENCE OF ADAMANTINOMATOUS CRANIOPHARYNGIOMA CYST FLUID. (23rd April 2019) - Vijmasi, Trinka; Prince, Eric; Whelan, Ros; Griesinger, Andrea; Donson, Andrew; Staulcup, Susan; Hoffman, Lindsay; Foreman, Nicholas; Handler, Michael; Hankinson, Todd
Abstract: INTRODUCTION: Pediatric Adamantinomatous Craniopharyngioma (ACP) is well known for its association with poor quality of life in young patients. Biologically guided therapies are currently unavailable. We and others have shown that the ACP tumor microenvironment is infiltrated with immune cells and that ACP cyst fluid (CF) is enriched with cytokines. To identify potential targeted therapies, we seek to understand the response of normal human T-lymphocytes to ACP cyst fluid. METHODS: Cyst fluid was collected intraoperatively from pediatric ACP patients. Human T- cells enriched from PBMC fractions of healthy donors were activated by CD3/CD28/CD2 co-stimulation and cultured in IL-2 supplemented conditioned media containing either ACP CF at 10% or no cyst fluid for 24 hours, after which cells were placed in fresh media. After 48 hours, the supernatants were collected for IL-6 ELISA and the cells were immunolabelled for flow cytometry. RESULTS: CF treated T-cells demonstrated decreased IL-6 secretion compared to control media treated T-cells (124.8±10.9 pg/mL vs 231.25±30.6 pg/mL; P=0.04). The proportion of Helper T-cells double positive for CD25 and CD137 (CD4+CD25+CD137+) was decreased with CF treatment (61.0% ± 3.6 vs 72.5%± 0.2; P=0.04). The proportion of Cytotoxic T-cells double positive for CD25 and CD137 (CD8+CD25+CD137+) was also decreased with CF treatment (21.0% ± 0.1 vs 36.3% ± 1.1; P=0.003). CONCLUSION: This study characterizes the response of T-cells under the influence of ACP cyst fluid. The cytokine milieu of ACP cyst fluid appears to have immunomodulatory effects on activated T-cells. The decrease in IL-6 secretion and markers of T-cell activation may indicate an immunosuppressive environment, thus supporting the paradigm for compromised tumor immunosurveillance in pediatric ACP. Further studies to characterize immune cells and their extensive cytokine secretory profile in response to ACP cyst fluid, in order to more completely understand ACP immunopathology, are underway.